Palladium-mediated site-selective Suzuki-Miyaura protein modification at genetically encoded aryl halides. - Spicer, C; Davis, B (2011)
Site-specific genetic incorporation of unnatural p-halophenylalanine amino acid residues as 'tags' coupled with Pd(0)-mediated Suzuki-Miyuara 'modification' has been enabled by discovery of an effective small molecule palladium scavenger.